The Role of Elementary Teachers in Developing 21st Century Skills: Creativity, Collaboration, Communication, and Critical Thinking - Ibrahim; Maimun, Maimun; Bahtiar, Bahtiar (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This research aims to explore the role of elementary school (SD) teachers in Mataram City in developing 21st century skills, with a focus on creativity, collaboration, communication and critical thinking. The research method used was a survey using a questionnaire to 100 elementary school teachers as respondents. Data were analyzed descriptively quantitatively and qualitatively to evaluate the extent to which teachers implemented 21st century skills development practices in their classrooms. The research results show that teachers show significant commitment in facilitating student creativity with an average score of 75%, as well as strong implementation of collaboration with an average score of 85%. Nevertheless, challenges such as limited resources and institutional support are still obstacles that need to be overcome to maximize the effectiveness of 21st century skills development in elementary schools. This research provides valuable insights for the development of more supportive education policies in the future.